1999
DOI: 10.1002/(sici)1097-4636(19990915)46:4<458::aid-jbm3>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Reactive capsule formation around soft-tissue implants is related to cell necrosis

Abstract: Low-density polethylene disks with smooth or course surfaces were implanted in the abdominal wall of rats, and the tissue response was evaluated after 1, 6, or 12 weeks. Cell damage was detected by two different methods. Cells with increased membrane permeability could be identified using fluorescence microscopy by injection of propidium iodide prior to the killing of the rats. Second, cell death was verified by detection of DNA fragmentation. At 1 week a considerable number of the interfacial cells was staine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 44 publications
3
19
1
Order By: Relevance
“…This is in accordance with previous studies showing that when both material and surface texture are varied, the surface texture appear to be the predominant factor relative to the induced tissue response [30], [31]. There are several reports indicating that structured and/or porous implant surfaces are favorable as compared with planar ones [29], [34], [40], [44]- [49]. It is conceivable that the different surface structures of the implants elicit different macrophage responses, which in turn may induce different tissue reactions by producing different secretion products such as: chemotactic agents for other cells, growth factors which stimulate the collagen production by the fibroblasts and neutral proteases which may affect the implant surface [50], [51] leading to different foreign-body formation including the thickness of the reactive capsule.…”
Section: A Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in accordance with previous studies showing that when both material and surface texture are varied, the surface texture appear to be the predominant factor relative to the induced tissue response [30], [31]. There are several reports indicating that structured and/or porous implant surfaces are favorable as compared with planar ones [29], [34], [40], [44]- [49]. It is conceivable that the different surface structures of the implants elicit different macrophage responses, which in turn may induce different tissue reactions by producing different secretion products such as: chemotactic agents for other cells, growth factors which stimulate the collagen production by the fibroblasts and neutral proteases which may affect the implant surface [50], [51] leading to different foreign-body formation including the thickness of the reactive capsule.…”
Section: A Discussionsupporting
confidence: 91%
“…Both materials will be oxidized naturally in air or in a biological environment. In addition, cell damage including increased membrane permeability was identified using flourescence microscopy after propidium iodide injection [40]. …”
Section: Tissue Reactions Evoked By Porous and Planementioning
confidence: 99%
“…This is in accordance with previous studies that demonstrated pathological changes in the retina in vivo, primarily in parts more likely to have been in direct contact with the gel [37], suggesting at least in part a toxic or immunological response. Recently, clinical use of Bio-Alcamid® in reconstructive surgery has become increasingly controversial due to late complications such as inflammation, infection and excessive capsule formation [45][46][47][48].…”
Section: Our Previous Results and Our Hypothesismentioning
confidence: 99%
“…A simple experiment [11] with rods of 1 mm in diameter, but different shapes implanted into rats showed that triangular polymer implants with sharp edges caused significantly higher cellular responses and acid phosphatase enzyme activity than square or round implants. Around implanted polyethylene disks with coarse surface in rats, a significant larger number of PI (propidium iodine stained) -positive cells with increased permeability were found in the tissue adjacent to the edges of the implant, when compared to implants with smooth surface [12]. A microsphere with an absolute smooth surface absorbs proteins and becomes slowly covered with collagen fibers.…”
Section: Surface Structurementioning
confidence: 99%